A qualitative review of parents' perspectives on the value of CAEP recording in influencing their acceptance of hearing devices for their child. (3rd July 2019) - Mehta, Kinjal; Mahon, Merle; Watkin, Peter; Marriage, Josephine; Vickers, Debi
Abstract: Objective: To obtain a parental perspective on how audiological tests, including recording cortical auditory-evoked potentials (CAEP) to speech sounds, influenced their uptake of hearing devices for their infant. Design: A focus group was established by parents of hearing-impaired children. A facilitator explored how audiology tests influenced their understanding and management of hearing loss in their child and their acceptance of hearing aids or cochlear implant referral. The views were transcribed and thematic analysis was used to understand key topics. Study samples: Eight sets of parents participated. Their children had been enrolled in an audiology pathway that included CAEP testing. The sample included six children who were aided, one child who was going through the implant assessment and one child who was implanted. Results: Parents reported that it was important for them to understand the test results because this influenced acceptance of hearing aids and cochlear implant assessments. Seven sets of parents had not understood ABR results, while six reported that CAEPs had helped them to understand their child's hearing and need for intervention. Conclusion: Compliance with early hearing aid use and referral for cochlear implant depends upon parents' understanding of their infant's hearing loss by including CAEPs in the audiology pathway.